Preparing roadmap for branding Pushkar Gulab - Dutt, Som (Indian Horticulture, 2019)
A meeting with Rose growers of Ghodakheda village, Chittorgarh district, 130 km away from Udaipur, was held on 5 May 2018. Twenty-five farmers participated in meeting to discuss and prepare a roadmap for promoting rose (Rosa bourboniana) or Pushkar Gulab.